Dual Phases of Respiration Chain Defect-Augmented mROS-Mediated mCa2+ Stress during Oxidative Insult in Normal and ρ0 RBA1 Astrocytes - Tsung-I Peng (Oxidative Medicine and Cellular Longevity, 2013)
Mitochondrial respiratory chain (RC) deficits, resulting in augmented mitochondrial ROS (mROS) generation, underlie pathogenesis of astrocytes. However, mtDNA-depleted cells (ρ0) lacking RC have been reported to be either sensitive or resistant to apoptosis. In this study, we sought to determine the effects of RC-enhanced mitochondrial stress following oxidative insult. Using noninvasive fluorescence probe-coupled laser scanning imaging microscopy, the ability to resist oxidative stress and levels of mROS formation and mitochondrial calcium (mCa2+) were compared between two different astrocyte cell lines, control and ρ0 astrocytes, over time upon oxidative stress. Our results showed that the cytoplasmic membrane becomes permeated with YO-PRO-1 dye at 150 and 130 minutes in RBA-1 and ρ0 astrocytes, respectively. In contrast to RBA-1, 30 minutes after 20 mM H2O2 exposure, ρ0 astrocytes formed marked plasma membrane blebs, lost the ability to retain Mito-R, and showed condensation of nuclei. Importantly, H2O2-induced ROS and accompanied mCa2+ elevation in control showed higher levels than ρ0 at early time point but vice versa at late time point. Our findings underscore dual phase of RC-defective cells harboring less mitochondrial stress due to low RC activity during short-term oxidative stress but augmented mROS-mediated mCa2+ stress during severe oxidative insult.